Therapeutic Management of Preputial Prolapse in Gir Bulls - Vadalia, J.V.; Tank, P.H.; Patel, J.S.; Fefar, D.T.; Padaliya, N.R. (The Indian Journal of Animal Reproduction, 2021)
Traumatic injury to prepuce followed by its contamination and infection are the main etiologies for the preputial prolapse in Gir bulls. All the six breeding Gir bulls under study had common anatomical/structural deformities of the preputial sheath. The medical/clinical management was carried out in bulls affected with 2nd degree preputial prolapse. The animals were instituted injection Streptopenicillin 5.0 g IM; injection Ceftriaxone and Tazobactam @ 5 mg/kg IM; injection Meloxicam @ 0.2 mg/kg IM and antiseptic dressing of the prepuce was done with 5 % solution of Povidone iodine. All the bulls recovered uneventfully within a week after treatment and were given sixty days of sexual rest after treatments to prevent further injury and reoccurrence of the preputial prolapsed condition. The outcome of present study suggests that the acute cases of 2nd degree preputial prolapse may recover with medical management and do not need surgical intervention.